Pemanfaatan Media Sosial dalam Optimalisasi Pembelajaran Daring di Desa Gunungpring - Qurotul Aini; Milna Wafirah; Falakhunnisa (Khidmatan, 2021)
Social media as a brave learning media is still rarely done by the people of Gunungpring Village. Therefore, the assistance was carried out this time to optimize online learning by using social media. This empowerment assistance uses the ABCD (Asset-Based Community Development) approach using several stages: discovery, dream, define, design, and destiny. Because in this new normal era, parents are minimizing expenses, then the author provides a solution by using social media, which is free but has many advantages, namely telegram. With the assistance program in the form of a telegram for learning media, children are expected to use their original cellphones to play games. Still, now children are taught to use mobile phones to know so that this potential can make children more effective in carrying out learning at home.